The therapeutic effects of dendrobium officinale polysaccharides on diabetes mellitus: from the perspective of gut microbiota - Wan, Jinyuan; Lin, Ruihe; Wu, Qiang (Frontiers in Endocrinology, 2025)
Dendrobium officinale is a traditional Chinese medicinal herb that has been extensively documented in classical medical texts for its effectiveness in treating diabetes mellitus. Modern pharmacological studies have shown that it possesses antitumor, antioxidant, immunomodulatory, and blood glucose- and lipid-lowering effects. Dendrobium officinale polysaccharides (DOPs), the main bioactive constituent of this herbal medicine, interact with the gut microbiota to reshape microbial composition, restore intestinal barrier integrity, modulate mucosal immunity, and ultimately ameliorate metabolic disorders. This review highlights the structural characteristics and bioactivities of DOPs, as well as the mechanisms by which gut microbiota are involved in the pathogenesis of diabetes mellitus. In particular, we point out that DOPs have significantly improved metabolic indicators related to diabetes by regulating intestinal microbiota. It aims to clarify the benefits of DOPs in ameliorating diabetes mellitus through gut microbiota modulation and provide new perspectives for its potential development as a prebiotic and for future clinical applications.